Performance of cassava planting materials produced using the "Semi Autotrophic Hydroponic" technology in the laboratory and across locations in the Democratic Republic of Congo - Binzunga, M.M. (Jomo Kenyatta University of Agriculture and Technology, 2024)
Cassava (Manihot esculenta Crantz)) is a crucial food crop in D.R. Congo, sustaining over 70% of the population and serving as a primary income source. However, the cassava seed system faces the challenge of a low propagation rate associated with an extended growing cycle. This research aimed to contribute to the improvement of the cassava seed system in D.R. Congo using stem cuttings provided by SAH technology. Two experiments assessed plantlet performance using two types of substrates. Experiment 1, employing a split-plot design, used four genotypes (IB961089A, MM060083, Nase14, and Albert28) and four single substrates: KlasmannTS3 (K), Vermiculite (V), Local Peat (P), and Sawdust (S). It involved three subculture periods lasting four weeks, with data collection on survival, height, leaf, internode, and cutting numbers. Experiment 2, following a similar design, investigated the performance of three genotypes (IB961089A, IBA070520, and IBA980555) under single substrates (K, V, and P) and their combinations (K25P75, V25P75, and V10P90). The field experiment in Mulungu and Kiliba utilized SAH-derived plantlets employing a 4 x 4 split-plot design. Data were collected on survival, growth parameters, and stem length at different months after planting. Finally, a simple cost analysis was carried out, comparing the production cost of SAH-derived plantlets to that of producing cutting sunder the conventional propagation method. Experiment 1 revealed substrate significantly influenced survival rates, surpassing 90% (p<0.05), showing the highest number of cuttings of 70.4 in three months, representing a ratio of 1:4 with the genotype MM060083 (p<0.001). Experiment 2 showed K25P75 did not differ from single KlasmannTS3, with the highest survival rate and an increase of 80.5 cuttings, representing a ratio of 1:4 with IBA961089A. The superior effect of the substrates was attributed to their favorable properties, allowing rapid plantlet growth. Field results indicated that Kiliba recorded a higher survival rate of 81.3% compared to Mulungu's73.8%. Across locations, MM060083 had the highest survival, exceeding 80%, whileNase14 had the lowest. The check-cutting method demonstrated the highest survival of over 90% compared to SAH-derived plants, but KlasmannTS3 had the highest among the SAH at Kiliba (85.4%). The highest stem length was obtained at Mulungu (17.5 m) compared to Kiliba's 10.5 m at 12 MAPs. Nase14 achieved the highest stem length of 17.7 m per plot, while IBA961089A had the lowest at 9.3 m at 12 MAPs. SAH-derived plants caught up with conventional checks across locations by 12 MAPs. The use of combined substrates, particularly K25P75, demonstrated an equal unit cost to that of the conventional mini stem, both amounting to USD 0.07. These findings provide relevant insights into policymakers' decisions to promote efficient cassava propagation method for sustainable agriculture, enhance food security, and promote economic development in D.R. Congo.